Molecular hydrogen inhalation modulates resting metabolism in healthy females: findings from a randomized, double-blind, placebo-controlled crossover study - Grepl, Pavel; Botek, Michal; Krejčí, Jakub; McKune, Andrew (Medical gas research, 2025)
Initially, molecular hydrogen was considered a physiologically inert and non-functional gas. However, experimental and clinical studies have shown that molecular hydrogen has anti-inflammatory, anti-apoptotic, and strong selective antioxidant effects. This study aimed to evaluate the effects of 60 minutes of molecular hydrogen inhalation on respiratory gas analysis parameters using a randomized, double-blind, placebo-controlled, crossover design. The study was conducted at Faculty of Physical Culture, Palacký University Olomouc from September 2022 to March 2023. Twenty, physically active female participants aged 22.1 ± 1.6 years who inhaled either molecular hydrogen or ambient air through a nasal cannula (300 mL/min) for 60 minutes while resting were included in this study. Metabolic response was measured using indirect calorimetry. Breath-by-breath data were averaged over four 15-minute intervals. Compared with placebo (ambient air), molecular hydrogen inhalation significantly decreased respiratory exchange ratio and ventilation across all intervals. Furthermore, the change in respiratory exchange ratio was negatively correlated with body fat percentage from 30 minutes onwards. In conclusion, 60 minutes of resting molecular hydrogen inhalation significantly increased resting fat oxidation, as evidenced by decreased respiratory exchange ratio, particularly in individuals with higher body fat percentages.
Keywords: dospělí; Healthy Volunteers; Female; klinické křížové studie; vodík; body fat; placebo; fat oxidation; Adult; mladý dospělý; ženské pohlaví; Rest; zdraví dobrovolníci pro lékařské studie; lidé; metabolic flexibility; dvojitá slepá metoda; respiratory exchange ratio; odpočinek; Cross-Over Studies; Hydrogen; Double-Blind Method; Young Adult; Placebos; mitochondria respiration; aplikace inhalační; Administration, Inhalation; Humans